2015
DOI: 10.1007/s12529-015-9508-9
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Neighborhood Environment Influences, Physical Activity, and Active Transportation to/from School across African American, Latino American, and White Girls in the United States

Abstract: Background Neighborhood environment influences may be particularly important for understanding physical activity (PA) patterns across ethnic subgroups of early adolescent girls. Purpose This study examined relationships between neighborhood variables, moderate to vigorous physical activity (MVPA), and active transportation to/from school across African American, Latino American, and White early adolescent girls living in an urban/suburban community in the northwestern U.S.A. Relations between the neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Ammouri et al () examined environmental opportunities for PA and found a significant direct effect on self‐reported PA among female adolescents (β = .18). Likewise, Duncan, Strycker, Chaumeton, and Cromley () reported significant direct effects for perceived accessibility to neighborhood facilities on accelerometer‐measured MVPA (β = .22) among female adolescents. Unfortunately, neither study reported CIs or standard errors, making it difficult to compare effects to the current study.…”
Section: Discussionmentioning
confidence: 95%
“…Ammouri et al () examined environmental opportunities for PA and found a significant direct effect on self‐reported PA among female adolescents (β = .18). Likewise, Duncan, Strycker, Chaumeton, and Cromley () reported significant direct effects for perceived accessibility to neighborhood facilities on accelerometer‐measured MVPA (β = .22) among female adolescents. Unfortunately, neither study reported CIs or standard errors, making it difficult to compare effects to the current study.…”
Section: Discussionmentioning
confidence: 95%
“…When considering how to address disparities in obesity among low-income Latino adolescents, consideration must be given to barriers and facilitators to PA for this population. Factors that have been quantitatively found to influence youth PA behaviors in diverse populations include neighborhood safety (Chaparro et al, 2019;Forsyth et al, 2015), access to public parks and facilities (Duncan et al, 2016;Galvez et al, 2013), support and modeling from family members (Christofaro et al, 2018;Eisenberg et al, 2014;Gallo et al, 2017;Wang et al, 2019), and school policies related to physical education (Mayorga-Vega et al, 2018). A research report from Salud America!, the Robert Wood Johnson Foundation Research Network to Prevent Obesity Among Latino Children, found that fewer Latino families report that their neighborhoods are safe places for children to play and that Latino neighborhoods are less likely to have recreational facilities than White neighborhoods (Swanson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Facilities for sports and recreation (e.g., fitness centres, recreation centres, tennis courts, basketball courts, parks and playgrounds) can facilitate public health by providing valuable places for engaging in physical activities [ 9 ]. Availability of these facilities has been shown to increase engagement in physical activities from walking for leisure to more vigorous activities across many population groups (e.g., children, youth and adolescents, adults and older adults) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. As such, common composite indices and methods for characterizing healthy neighbourhoods generally include some measure of availability of facilities for physical activity [ 3 , 5 , 22 ].…”
Section: Introductionmentioning
confidence: 99%